(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the relevance and importance of foreign language teaching for non-linguistic faculty students. The history of the development of vocationally oriented foreign language teaching is covered. The essence of professional foreign language teaching is defined. Approaches that include the professional-oriented education model, its goals and objectives, problems that arise in the educational process and ways to solve them are presented.